PENGARUH CITRA PERUSAHAAN DAN RELATIONSHIP MARKETING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PT. ASTRA INTERNASIONAL-MEDAN - Desma Erica Maryati Manik (Universitas Islam Islam Sumatera Utara, 2018)
This research is to investigate the influence of company image and relationship marketing on consumer purchasing decision at PT. Astra International Daihatsu, Branch Office S.M. Raja Medan. The research is a quantitative method while the questionnaire used for data collection. The sample of the study is 100 out of 596 counsummers as population in 2016 using simple random sampling. Multiple linear regression and coefficient determination are used to analyze the data . The results show that partially the company image has significant positive effect on consumer purchasing decisions at PT. Astra International Daihatsu, SM Raja Medan Office Branch because tcount ttable (6.648 1.661). Partially, relationship marketing does not have an influence on company image on consumer purchasing decision at PT. Astra International Daihatsu SM Raja Medan Office Branch because tcount ttable (0.683 1.661). Simultaneously, company image and relationship marketing have a significant positive effect on consumer purchasing decisions at PT. Astra International Daihatsu SM Raja Medan Office Branch because Fcount Ftable (22.592 2.36). The coefficient of determination shows the influence of these two variables is 31.8% and the remaining 77.3% is influenced by other factors that come out of this research such as promotion, price, customer satisfaction and so on.